Selection of Bradyrhizobium strains for cowpea growing in an acid soil (LVA) of the semiarid region of Brazil - Stamford, Newton Pereira; Vieira, Iraci Maria de Mendonça Bastos; Santos, Diércules Rodrigues dos; Santos, Carolina Etienne de Rosàlia e Silva (Pesquisa Agropecuaria Brasileira, 2014)
To evaluate the efficient dinitrogen-fixing ability of Bradyrhizobium spp strains for cowpea, selected in previous assays using Leonard jars at high temperature regime, a greenhouse experiment was carried out with two cowpea cultivars UPA 202 and Pitiuba) growing in an acid LVA sandy-loam texturized soil, located in "Chapada do Araripe", in the semiarid zone of Brazil. Three lime treatments (0, 2 and 4 CaCo3 t/ha) were applied, and seeds were inoculated with NFB 09, NFB 36, NFB 91 and CB 756 strains, with a basal fertilization of phosphorus. The results showed that lime addition (2 t/ha) increased nodulation, total N accumulated and plant dry matter, and 4 t/ha rate decrease all the parameters. Correlation between total N and nodules weight at the various lime rates and with the different strains was observed. Inoculation affected positively nodulation, total N and dry matter yield with NFB 09 showing the best results.